The Impact of Remittances from Circular Migration on the Consumption Behavior of Families Left Behind: Case Study on Migrant Families Migrating from Madura to Jakarta - Rahman, Ghiffary Muhammad Emier; Ashar, Khusnul; Satria, Dias (AIBPM Publisher, 2023)
The focus of this research is how remittances from Madura to Jakarta affect the spending habits of families left behind. Six people are available for interview. From the interviews, the informants shared the experiences of the families and the migrants themselves in managing the remittances earned. The interviews were recorded, transcribed, and analyzed using qualitative methods with a descriptive approach. The results of the interviews show that families are very happy and supportive of their members becoming circular migrant workers. This happens because of the limited job opportunities available in Madura, and the needs of life that must be met. Before a family member migrated to work, the family's life was so poor that they could not fulfill some family needs. But after a family member migrated, their economic life and even social life became better. The money earned by the family is used not only for consumption of daily needs, but the family prioritizes investment and most of them invest by buying gold, jewelry, land, and opening or expanding existing businesses. In addition, the families also prioritize their children's education so that they can go to school to the highest level possible.